A microporous silk carbon–ionic liquid composite for the electrochemical sensing of dopamine. Issue 8 (16th March 2016) - Wang, Min; Bai, Lu; Zhang, Lingling; Sun, Guangping; Zhang, Xiaowei; Dong, Shaojun
Abstract : A metal-free silk carbon–ionic liquid composite, synthesized from natural silk cocoons, was prepared for electrochemical determination of dopamine. Abstract : Porous silk carbon (Silk C) was obtained through carbonization and KOH activation of natural silk cocoons. The as-prepared Silk C presented the good characteristics of a large surface area ( S BET : 2854.53 m 2 g −1 ) and a high volume of pores (1.54 cm 3 g −1 ) with uniform micropores (2.5 nm) and multiple defects. The metal-free silk carbon–ionic liquid (Silk C–IL) composite, synthesized by modifying Silk C with ionic liquid through non-covalent (π–π) interactions under grinding conditions, was prepared for electrochemical determination of dopamine (DA). The detection limit of DA was 79 nM (S/N = 3) with a linear range from 0.6 μM to 140 μM. Meanwhile, the as-made Silk C–IL/GCE presented good selectivity for DA detection from other possible interferences, such as ascorbic acid, glucose and uric acid. Furthermore, the Silk C–IL/GCE was also successfully used for the detection of DA in fetal bovine serum and dopamine hydrochloride injection samples.